Household shocks and consumption smoothing: Evidence from Northern Bangladesh - Bakhtiar, M. Mehrab; Rabbani, Atonu (International Food Policy Research Institute, 2021)
Poor households in rural Bangladesh often face concurring idiosyncratic and aggregate shocks, which have adverse impacts on their income and consumption. In this study, we investigate the transmission channels, coping responses, and economic consequences of different shocks including idiosyncratic adverse health events and aggregate agricultural productivity shocks. We use a balance panel data of 5,655 rural households – interviewed every year between 2010 and 2013 – in northern Bangladesh. We estimate the effects of adverse health shocks on the consumption levels of the poor households in a multi-shock framework. We take advantage of the panel data and use fixed effect models to control for unobserved household-level confounders and potential endogeneity. We further examine effects of shocks to agricultural wages on consumption using rainfall as an instrument. We further carry out a number of robustness checks to understand how sensitive our models are to different alternate specifications. Results indicate that households smooth their consumption after experiencing adverse health shocks, with and without the parallel incidence of other types of shocks. Consumption smoothing occurs despite households experiencing a significant decrease of wage income, which is possibly driven by an increase in informal loans from village money lenders and households’ social networks. To evaluate the effect of a different type of income shock on consumption, we use rainfall as an exogenous instrument for agricultural income. Results indicate that while higher rainfall leads to a significant increase in agricultural income, it does not translate to higher food expenditure for households. Together, these findings offer suggestive evidence that, in this particular setting, households appear to smooth food consumption in the face of income shocks. Poor households rely on formal and informal, potentially costly channels and exploit existing social networks to insure themselves against adverse shocks. The findings highlight the importance of developing a better framework and a more effective implementation of equitable social safety net policies.